2023
DOI: 10.24912/je.v28i1.1266
|View full text |Cite
|
Sign up to set email alerts
|

Insentif Pajak Dan Tingkat Kepercayaan: Pengaruhnya Terhadap Kepatuhan Wajib Pajak

Abstract: The research objective was to find out whether there was an effect of tax incentives on MSME taxpayer compliance during the COVID-19 pandemic with the level of trust in the government as a moderating variable. The sampling technique used is Accidental Sampling. The research sample are 100 respondents. Data collection through distributing questionnaires. Statistical testing to support Structural Equation Modeling (SEM) analysis using SmartPLS version 3.0 software. The results of the study document that tax ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…The results of this study are in accordance with the research of Sartika, Afifah, and Sari (2021) which states that the provision of motor vehicle tax incentives (PKB) during the COVID-19 pandemic had a significant effect on taxpayer compliance in paying motor vehicle taxes owed. In addition, the existence of tax incentives as a form of tax relief can provide reactions and behavior of taxpayers to care about taxes so that they comply with taxpayer compliance (Amah et al, 2023) to fulfill their tax obligations. Therefore, it can be concluded that PKB incentives have a significant effect on taxpayer compliance.…”
Section: Effect Of Pkb Fiscal Incentives On Compliance With Pkb Taxpa...mentioning
confidence: 99%
“…The results of this study are in accordance with the research of Sartika, Afifah, and Sari (2021) which states that the provision of motor vehicle tax incentives (PKB) during the COVID-19 pandemic had a significant effect on taxpayer compliance in paying motor vehicle taxes owed. In addition, the existence of tax incentives as a form of tax relief can provide reactions and behavior of taxpayers to care about taxes so that they comply with taxpayer compliance (Amah et al, 2023) to fulfill their tax obligations. Therefore, it can be concluded that PKB incentives have a significant effect on taxpayer compliance.…”
Section: Effect Of Pkb Fiscal Incentives On Compliance With Pkb Taxpa...mentioning
confidence: 99%